2014
DOI: 10.1111/ecge.12056
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Innovation and Wage Inequality: New Evidence fromCanadian Cities

Abstract: In this article, we examine the link between innovation and earnings inequality across Canadian cities over the 1996-2006 period. We do so using a novel data set that combines information from the Canadian long-form census and the United States Patent and Trademark Office. The analysis reveals that there is a positive relationship between innovation and inequality: cities with higher levels of innovation have more unequal distributions of earnings. Other factors influencing differences in inequality include ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 94 publications
(113 reference statements)
1
57
0
3
Order By: Relevance
“…Florida and Mellander (2014) studied the determinants of wage inequality in a cross-section of US MSAs and found that the share of high-technology industries is a reliable predictor of wage inequality, if not income inequality. Panel studies have also unveiled a positive relationship between innovation and inequality for European regions (Lee & Rodríguez-Pose, 2013;Lee, 2011) and Canadian cities (Breau et al, 2014). This was, however, not the case of US cities (Lee & Rodríguez-Pose, 2013), where higher levels of innovation…”
Section: High-technology Growth and Povertymentioning
confidence: 99%
See 1 more Smart Citation
“…Florida and Mellander (2014) studied the determinants of wage inequality in a cross-section of US MSAs and found that the share of high-technology industries is a reliable predictor of wage inequality, if not income inequality. Panel studies have also unveiled a positive relationship between innovation and inequality for European regions (Lee & Rodríguez-Pose, 2013;Lee, 2011) and Canadian cities (Breau et al, 2014). This was, however, not the case of US cities (Lee & Rodríguez-Pose, 2013), where higher levels of innovation…”
Section: High-technology Growth and Povertymentioning
confidence: 99%
“…Breau, Kogler, & Bolton, 2014;Donegan & Lowe, 2008;Fowler & Kleit, 2013;Lee, 2011;Lee & Rodríguez-Pose, 2013). It also makes a number of more specific contributions to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…While they provide a valuable descriptive account of trends in urban inequality, like Bourne (1993), they do not detail the causes of inequality. Mitchell and Soroka (1993), Soroka (1999) and more recently Bolton and Breau (2012) and Breau, Kogler, and Bolton (2014) have investigated urban patterns of inequality using multivariate modeling frameworks that control for a multitude of explanatory factors. Myles, Picot, and Pyper (2000) and Heisz and McLeod (2004) provide an overview of neighborhood income inequality across Canada's largest cities and argue that the relative stability in national-level inequality in the 1980s and early 1990s conceals important variation and changes in the distribution of income across neighborhoods.…”
Section: The Empirical Literaturementioning
confidence: 99%
“…developments in the patent data literature may provide opportunities to further explore the link between greater innovation and earnings inequality at the regional level (see, for instance, Breau et al, 2014).…”
Section: Dep Variable ¼ Ginimentioning
confidence: 99%
“…However, British cities lack the most powerful levers to address and alleviate inequality through the tax and benefits system. A growing body of literature considers the determinants of urban inequality, with studies focusing on Canada (BOLTON and BREAU, 2012;BREAU et al 2014), the United States (GLAESER et al 2009;FLORIDA and MELLANDER, 2014) and Swedish local labour markets (KORPI, 2008). In the UK, work has considered employment polarisation (JONES and GREEN, 2009) and wage inequality (DICKEY, 2001;TAYLOR, 2006;DICKEY, 2007;STEWART, 2011), but only at a regional level.…”
Section: Introductionmentioning
confidence: 99%